Decoupled recursive‐least‐squares technique for extraction of power system synchronised phasors under fault conditions. Issue 11 (1st November 2013) - Sadinezhad, Iman; Agelidis, Vassilios G.
Abstract : This study presents application of the decoupled recursive‐least‐squares (DRLS) technique for extraction of power system synchronised phasors under fault conditions. The proposed DRLS technique demonstrates robust performance during faults, subsequent operation of circuit breakers and reclosing of a transmission line. The proposed DRLS technique also significantly reduces the computational burden of the conventional RLS technique for implementation on digital signal processors (DSPs). The modification of decomposition of single‐phase into orthogonal components frequency estimation technique for three‐phase power systems is also applied to adapt the DRLS estimation with frequency drifts. The performance of the proposed DRLS technique has been evaluated through presetting selected simulation results in DigSilent Power Factory and MATLAB‐Simulink. DSP implementation of the DRLS technique also confirms considerable computational efficiency improvement when compared with that of the conventional RLS technique.